If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-3(5x-5)=65
We simplify the equation to the form, which is simple to understand
5x-3(5x-5)=65
Reorder the terms in parentheses
5x+(-15x+15)=65
Remove unnecessary parentheses
+5x-15x+15=+65
We move all terms containing x to the left and all other terms to the right.
+5x-15x=+65-15
We simplify left and right side of the equation.
-10x=+50
We divide both sides of the equation by -10 to get x.
x=-5
| 4r^2+20r+24=0 | | 9x^2+16y^2+54x-32y-47=0 | | 6+9h=20+2h | | c=15(47) | | 4-a/6=-16 | | f(x)=-14x^3+9x^2-2 | | 0.02(y-3)+0.14=0.04y-0.03(30) | | 4a^2+24a+36=0 | | 3*-12=36 | | 0.2x+7.2=5.9 | | (x+1)(x-1)=5(x+1) | | 5x-4(-x+8)=-31 | | 5x^2-x-54=0 | | 0.02(y-4)+0.14y=0.04y-0.03(30) | | 29-5x=4+7x | | 2*(x^2)+3*x-2000=0 | | x/6-4=16 | | 5x-x-54=0 | | 6(x-6)+6=3(x-7) | | (x-3)(2x+3)=5 | | -6(0.1x+0.4)-1.3=-0.1 | | 5x^2+13x-1= | | -3+7(x-1)=12x+2-5x | | 4x+6=42-2x | | 1-7=x-x | | .58y-.25=2y-1.7 | | -2(2x-1)+7=-4x+9 | | -8x+15=-10x+5 | | n-7=3 | | 7x-3(6-x)=16 | | 4x-1=-2x+11 | | 41=16-6-x |